Avaliação da atividade antioxidante e antimicrobiana do extrato de semente de chia e sua aplicação em linguiça frescal - Scapin, Gabrielle (2014)
The present study had as object verify the antioxidant activity of chia seed extracts (Sálvia hispânica) and its antioxidant effect in pork sausage. First of all, it was held the chemical composition of the chia seed. It presented high dietary fiber content, protein and lipids and low moisture content. After that, it was elaborated hydroethanolic extracts by stirring, using different ethanol concentrations and temperatures. In the extracts obtained were performed analyzes to measure total phenolic compounds, total flavonoids and antioxidant activity in vitro through DPPH and FRAP methods. The extract obtained from stirring using ethanol 80% as solvent and 60ºC temperature, was the one that got the best antioxidants features, so, this one was applied in concentrations of 1%, 1,5% and 2% in pork sausages. To characterize the meat product, were held analyzes to measure pH, color, TBARS values and microbiological analysis. The sensorial analysis was evaluated by the test of acceptability with hedonic scale of seven points, and purchase intent test. The results obtained in the proximate composition, as well as in the microbiological analyzes to positive Staphylococcus coagulase, coliforms between 35ºC and 45ºC, Samonella sp e Clostridium sulfito products reducer are according to what is required by Brazilian law. The sausage pH showed an increase throughout time in storage. Regarding color, the product showed a staining tendency to browning. In the end of 28 days of storage, the TBARS values was 1,12 mg of MDA/kg to the control treatment (0% of chia extract). The chia seed extract did not present effects over the microbiological stability along the storage, measured by counting the total mesophilic aerobic microorganisms and psicrotrofics. The sensorial features stability was kept, showing good acceptability by consumers. Therefore, we can conclude that the chia seed extract (Sálvia hispânica) was able to inhibit the lipid oxidation of pork sausage, which suggests its applicability as a natural antioxidant source.